1998
DOI: 10.1046/j.1365-2222.1998.00255.x
|View full text |Cite
|
Sign up to set email alerts
|

Indoor airborne fungal spores, house dampness and associations with environmental factors and respiratory health in children

Abstract: Indoor exposure to certain fungal genera in winter was a risk factor for asthma, atopy and respiratory symptoms in children. On the other hand, no significant associations were seen between average viable or total spore concentrations and child health. Actual measurements of fungal spores predict health outcomes better than reported dampness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
250
1
5

Year Published

2003
2003
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 348 publications
(268 citation statements)
references
References 25 publications
12
250
1
5
Order By: Relevance
“…Results have shown null, weak, and significant positive associations among the two exposure types as well as inconsistencies across studies with respect to the taxa showing associations with home characteristics (Waegemaekers et al, 1989;Strachan et al, 1990;Wickman et al, 1992;Li and Hsu, 1997;Garrett et al, 1998;Ren et al, 2001;Chew et al, 2003;O'Connor et al, 2004). These inconsistencies could be secondary to geographic location, season of sampling, as well as housing types and construction materials.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Results have shown null, weak, and significant positive associations among the two exposure types as well as inconsistencies across studies with respect to the taxa showing associations with home characteristics (Waegemaekers et al, 1989;Strachan et al, 1990;Wickman et al, 1992;Li and Hsu, 1997;Garrett et al, 1998;Ren et al, 2001;Chew et al, 2003;O'Connor et al, 2004). These inconsistencies could be secondary to geographic location, season of sampling, as well as housing types and construction materials.…”
Section: Discussionmentioning
confidence: 95%
“…Numerous studies (primarily cross-sectional in design) involving older children and adults have reported at least one positive association between total airborne fungal or bacterial counts, or specific fungal taxa including Penicillium, Cladosporium, Aspergillus or Alternaria species, and respiratory symptoms including cough, wheeze and asthma (Platt et al, 1989;Strachan et al, 1990;Bjornsson et al, 1995;Li and Hsu, 1997;Garrett et al, 1998;Dharmage et al, 2001;Downs et al, 2001). Null findings in all age groups also have been reported for both airborne (Su et al, 2001) and dustborne fungi (Wickman et al, 1992;Verhoeff et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, attempts to correlate health outcomes with spore counts have not indicated strong associations. Furthermore, several field studies have shown that the concentrations of airborne fungal spores in mold problem buildings are not necessarily higher than in non-problem ones (Strachan et al, 1990;Nevalainen et al, 1991;Garrett et al, 1998;Chew et al, 2003). This indicates that spore concentrations may not be an adequate measure for fungal exposures.…”
Section: Introductionmentioning
confidence: 99%
“…A few studies have described a decrease in the levels of airborne microbial compounds as a result of such repair (Rylander, 1997). On the other hand, high airborne fungal concentrations have been associated with failure to remove indoor mold growth (Garrett et al, 1998).…”
Section: Introductionmentioning
confidence: 99%